Strategi dan Implementasi Komunikasi Dakwah Persuasif di Komunitas Punk Hijrah Bandar Lampung - Rosidi Rosidi; Nadya Amalia Nasution; Mubasit Mubasit; M Ihsan Solihin (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2023)
This study tries to explore the strategy and implementation of persuasif da'wah communication in the hijrah punk community. Participants in this study were hijrah actors, founders of the hijrah punk community, as well as administrators from the hijrah punk community. The research findings reflect that the hijrah punk community movement occurred communally and gave birth to a religious-based social movement. The hijrah punk community movement has built a new identity, namely as a religious youth who is closer to Islam and becomes a useful person. The hijrah punk community has the intention of making punk children in Bandarlampung City to know Islam with three main approach strategies, namely psychodynamic strategies that involve emotional and cognitive factors in persuasion. A sociocultural strategy that utilizes environmental factors, namely the friendship that exists between the administrators to preach. The meaning construction strategy focuses more on providing understanding by manipulating understanding without having to change the meaning, the goal is to simplify conveying persuasif messages with understandable analogies.